Exposure to leachates from post-consumer plastic and recycled rubber causes stress responses and mortality in a copepod Limnocalanus macrurus. (December 2021) - Lehtiniemi, Maiju; Hartikainen, Samuel; Turja, Raisa; Lehtonen, Kari K.; Vepsäläinen, Jouko; Peräniemi, Sirpa; Leskinen, Jari; Setälä, Outi
Abstract: Effects of household post-consumer plastics and tyre rubber on a Baltic Sea copepod Limnocalanus macrurus were assessed. Fragments of commercial recycled low-density polyethylene vegetable bags and rubber originating from recycled car tyres were incubated in seawater, and the copepods were exposed to the filtrate of the water. L. macrurus experienced erratic swimming behaviour and increased mortality in the filtrate of unwashed vegetable bags, containing elevated concentrations of alcohols, organic acids and copper. Responses of the antioxidant defence system (ADS) were recorded in copepods exposed to rubber treatments containing high concentrations of zinc. Significant responses in the ADS enzymes indicate that reactive oxygen species (ROS) formation was exceeding the detoxification capacity of the ADS which may further lead to prolonged state of oxidative stress. Observed effects of exposure on the biochemical level coincide with impaired swimming activity of the copepods, indicating possible irreversible cellular responses leading to behavioural changes and mortality. Graphical abstract: Unlabelled Image